Muslim Environmentalisms: Religious and Social Foundations by Anna M. Gade (American Journal of Islam and Society, 2020)
While the global environmental crisis has escalated rapidly in recent years, work at the intersection of Islamic Studies and Environmental Studies is a newly developing area, to which Anna Gade’s Muslim Environmentalisms: Religious and Social Foundations presents a significant contribution. While the most immediate readership of the work would be those interested in the intersection of those fields, the book makes a broad claim that critically engages with questions of boundaries and constructions of both fields and is of interest to scholars of Islam as well as non-Islamicists in the areas of Environmental Studies and  Environmental Humanities. The work is in conversation not only with previous Islamic Studies works on the environment, such as Seyyed Hossein Nasr’s several earlier works in this area as well as Sarra Tlili’s more recent Animals in the Qur’an, but also recent critical interrogations field-forming discourses such as Shahab Ahmed’s What Is Islam: The Importance of Being Islamic. As a scholar of Islam who is only newly becoming acquainted with the field of Environmental Humanities, I consider the text here most specifically in terms of its contribution to Islamic Studies, but it is important to note that the book has a broad readership beyond this area.Download